2014
DOI: 10.1121/1.4838975
|View full text |Cite
|
Sign up to set email alerts
|

Recognition memory in noise for speech of varying intelligibility

Abstract: This study investigated the extent to which noise impacts normal-hearing young adults' speech processing of sentences that vary in intelligibility. Intelligibility and recognition memory in noise were examined for conversational and clear speech sentences recorded in quiet (quiet speech, QS) and in response to the environmental noise (noise-adapted speech, NAS). Results showed that (1) increased intelligibility through conversational-to-clear speech modifications led to improved recognition memory and (2) NAS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 64 publications
2
22
0
Order By: Relevance
“…They interpreted this finding as reflecting stronger linguistic encoding when less processing was required to accurately identify the targets, consistent with our proposal that lexical information is encoded more robustly when the cost of normalization is smaller. Furthermore, Gilbert et al (2014) observed that overall intelligibility was not fully predictive of encoding strength (see also Mattys and Liss (2008)), consistent with our observation from Experiment 1 that processing dialect-specific information is costly even when word recognition is ultimately successful. Our results provide new evidence that the processing costs associated with normalization for dialect variation in noise play a critical role in lexical encoding strength: the presence of noise in Experiment 2 imposed a greater processing cost on the Northern forms, resulting in weaker encoding of the Northern forms in memory, relative to the Midland forms.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…They interpreted this finding as reflecting stronger linguistic encoding when less processing was required to accurately identify the targets, consistent with our proposal that lexical information is encoded more robustly when the cost of normalization is smaller. Furthermore, Gilbert et al (2014) observed that overall intelligibility was not fully predictive of encoding strength (see also Mattys and Liss (2008)), consistent with our observation from Experiment 1 that processing dialect-specific information is costly even when word recognition is ultimately successful. Our results provide new evidence that the processing costs associated with normalization for dialect variation in noise play a critical role in lexical encoding strength: the presence of noise in Experiment 2 imposed a greater processing cost on the Northern forms, resulting in weaker encoding of the Northern forms in memory, relative to the Midland forms.…”
Section: Discussionsupporting
confidence: 83%
“…For example, Church and Schacter (1994) observed significant repetition benefits with low-pass filtered stimulus materials in their implicit recognition memory task, but no significant repetition benefits with stimulus materials presented in the quiet in their explicit recognition memory task, suggesting differential processing of talker-specific information as a function of noise and/or task demands. More recently, Gilbert, Chandrasekaran, and Smiljanic (2014) found stronger explicit recognition memory in noise when the speech to be remembered was hyperarticulated. They interpreted this finding as reflecting stronger linguistic encoding when less processing was required to accurately identify the targets, consistent with our proposal that lexical information is encoded more robustly when the cost of normalization is smaller.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, delayed recognition memory tasks consistently demonstrate that encoding is poorer for speech listening task conditions that are more difficult (e.g., Wild et al, 2012; Zekveld et al, 2013; Gilbert et al, 2014; Van Engen and Peelle, 2014). The present study replicates these behavioral results: recognition memory was worse for words that had been presented in a lower compared to a higher SNR in Task 1.…”
Section: Discussionmentioning
confidence: 99%
“…Clear speech-a speaking style that is naturally and spontaneously adopted by speakers when they are aware their interlocutors are having difficulty understanding them-is more intelligible than conversational speech for a wide range of listeners in noisy conditions and, further, improves recognition memory for speech in quiet and in noise (Gilbert, Chandrasekaran, & Smiljanic, 2014;Van Engen, Chandrasekaran, & Smiljanic, 2012). Among those for whom intelligibility benefits have been documented are adults with normal and impaired hearing (Payton, Uchanski, & Braida, 1994;Picheny, Durlach, & Braida, 1985), older adults with hearing loss (Ferguson & Kewley-Port, 2002;Schum, 1996), nonnative speakers (Bradlow & Bent, 2002), and children with and without learning disabilities (Bradlow, Kraus, & Hayes, 2003).…”
mentioning
confidence: 99%